ANALISIS RISIKO OPERASIONAL PADA PERUSAHAAN PELAYARAN DALAM MEMENUHI PERMINTAAN KEBUTUHAN KAPAL - Angger Eka Bagus Aprilianto; Aditya Maharani; Fitri Hardiyanti (Proceeding Maritime Business Management Conference, 2022)
One of the sea transportation companies that serve dry bulk transportation. In its journey, the company has succeeded in delivering many types of transportation with various types of cargo. The success of the trip could not be separated from the intervention of the workers in the office, especially in terms ofsupply in meeting their needs. Almost every week, the ship makes requests to the office for supplies related to the needs needed. However, in the business process it is not uncommon for various kinds of risks to occur, so that it is necessary to do countermeasures. So this study aims to identify risks in the businessprocess of meeting the demand for ship needs and their mitigation strategies. The method used in this research is the House of Risk method. By using the House of Risk method, researchers can simultaneously identify, analyze, evaluate and determine mitigation strategies. The results of research on business processes in meeting the demand for ship needs obtained 21 risk events and 28 risk agents. And the House of Risk 1 produces 16 dominant risk agents. Then 20 mitigation strategies or preventive actions wereobtained at the House of Risk 2 stage.